Cryptosporidium spp. infections in livestock and wild animals in Azerbaijan territory - S. Mamedova; P. Karanis (IWA Publishing, 2021)
Cryptosporidium is an intracellular protozoan parasite, globally distributed and capable of infecting various vertebrate species, including humans as well as domestic and wild animals. Cryptosporidium is increasingly gaining attention as a human and an animal pathogen mainly due to its dominant involvement in worldwide waterborne outbreaks. The present paper reviews the current knowledge and understanding of Cryptosporidium spp. in terrestrial and water animals in Azerbaijan. HIGHLIGHTS First review on knowledge and understanding of Cryptosporidium spp. in terrestrial and water animals in Azerbaijan.; First review zoonotic Cryptosporidium species in Azerbaijan.; Crypto livestock, wildlife, amphibians, birds, and mammals.; An extensive report based on a comparative analysis of morphometric parameters of Crypto oocysts.; High prevalence rates in domestic and wild animals.;